Rhexis fixation of intraocular lens in a case of buphthalmos with cataract - Gupta, Parul Chawla; Singh, Rishi Raj; Pandav, Surinder Singh; Ram, Jagat (Nepalese Journal of Ophthalmology, 2016)
We describe a case of buphthalmos and coexisting cataract undergoing clear corneal phacoemulsification where a routinely available, normal sized lens was implanted using the novel technique of ‘Rhexis fixation of IOL’.Nepal J Ophthalmol 2016; 8(15): 71-73